Chinese Adolescents’ Conceptions of Teacher Authority and Their Relations to Rule Violations in School - Liu, Jianjin (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2018)
Based on the Social Cognitive Domain Theory, the paper explored the adolescents’ conceptions of teacher authority in different domains and their relations to rule violations in school. The main results are: 1) Adolescents viewed moral, conventional, and prudential issues as legitimately subject to teachers’ authority and personal issues as under personal jurisdiction, but they were equivocal about contextually conventional issues. 2) Seventh graders judged all acts as more legitimately subject to teachers’ authority, all rule violations as more negative than did older students. 3) Compared with adolescents from big cities, adolescents from rural area viewed moral, conventional, contextually conventional, and personal issues as more legitimately subject to teacher authority, and endorsed less personal jurisdiction over those issues; but there were no significant differences in moral domain. 4) Male subjects reported more violations in conventional and prudential domain. 5）Adolescents’ older age, less endorsement of legitimacy of teacher authority, and greater dislike for school predicted more teacher- and self-reported misconducts. Implications for moral education from these results were also discussed.
Keywords: Adolescents; Social Cognitive Domain Theory; conceptions of teacher authority; rule violations in school